Automatic Temperature Control System for Gray Oyster Mushroom Block Steamer - Ismail, Farah Sakinah; Alias Masek (Research and Innovation in Technical and Vocational Education and Training, 2021)
TAbstract: The purpose of this project is to design and develop the Automatic Temperature Control System product for Gray Oyster Mushroom Block Steamer. This was due to problems that occurred in controlling the temperature and monitoring time in the steaming process of mushrooms. In addition, based on preliminary survey, the Automatic Temperature Control System for Gray Oyster Mushroom Block Steamer is yet to be in the market. Thus, the main objective of the project is to design an automatic temperature control system for the gray oyster mushroom steamers using Blynk applications consisting of DS18B20 temperature detectors as well as developing software using microcontrollers. The project was developed based on the Engineering Design Process model, which is the phase of asking, imagine phase, plane phase, create phase and improve phase. Overall, the project has successfully worked as planned. The automatic temperature control system for this gray oyster mushroom steamer works when the temperature exceeds the set level the Blynk application will receive notification and the mushroom operator can control the heating of the fire through the Blynk app as well. So here mushroom entrepreneurs can monitor through smartphones. Therefore, with the operations of this circuit the mushroom operator can avoid losses from damage of the mushrooms. In fact, it is also relevant to help entrepreneurs toward technological entrepreneurship. Keywords: Gray Oyster Mushroom, Blynk, Temperature Control, DS18B20, Temperature sensor